Знаменитые столицы и города мира: справочное издание / сост. В. В. Лисюченко; В. Б. Гарин - Гарин В. Б. (Феникс, 2000)
Экземпляры: аб. (2002) / Инвентарный номер: 44077 / Цена: / Сис.шифр: 26.89(0) / Авт.знак: З-72 / ГРНТИ: 06.61.53 / ББК: 26.89(0)я2